Contacts and Discontinuities: Changing Aspects in Shimon Adaf’s Work - Lemberger, Dorit (Hebrew studies, 2014)
The writings of Shimon Adaf construct a hybrid, multicultural quasi-dialect that is unusual in Israeli literature in general and in the genre known as “Oriental Jewish literature” in particular. While Israeli Hebrew is hybrid by its very nature, there is a difference between hybridity deriving from instinctive use of the spoken language and that arising from an intentional, self-aware act designed to flout literary, and especially sociopolitical, conventions. In this article I shall demonstrate how Adaf’s use of imagery leads to unique, fresh literary and political positions. All Adaf’s protagonists are of Moroccan origin, from a small town on the periphery; they observe Israeli reality “from the outside.” They do not represent the “Oriental” voice that prevails in both fiction and scholarly writing by Jewish authors of non-European origin who delve into issues of discrimination, disenfranchisement, and other socioeconomic tensions. Adaf’s characters “cut loose” from acute current problems and via hybridity re-connect to bygone times. These characters raise universal, existential questions that do not stem from their belonging to a specific time and place, for example, those of relations obtaining between language and reality and of the possibility to change the latter by means of poetic language. Such problems are evoked by quotations from various literatures (Greek, English, German) and by the use of different strands of Hebrew: biblical, rabbinic, and Israeli. By employing metaphoric language, Adaf examines how the cultural norms in which language is steeped dictate modes of behavior and how we can influence the reformulation of these norms by the use of that very language.